Writing, society and culture in early Rus, c. 950-1300 - Franklin, Simon (Cambridge University Press, 2002)
This is the first comprehensive study of the origins and early uses of Russian writing, including analysis of a wide range of writings from a variety of perspectives. The impressive scholarship and idiosyncratic wit of this volume commend it to students and specialists in Russian history and literature alike.